An interface for integrated modelling capacity to incorporate Agricultural Production Systems sIMulator crop model predictions in Simile livelihood trajectory models - CGIAR Research Program on Forests, Trees and Agroforestry (2019)
The modellling capability has been developed and is available through the Simulistics website